(untitled) (Research, Society and Development, 2021)
Photovoltaic systems emerge as a solution to meet the energy demand in Brazil, in addition to bringing opportunity for economic growth, consequently the development of the industrial sector and companies installing photovoltaic systems that end up generating more jobs. Today, solar energy is the source of renewable energy that employs the most in Brazil. Employees who perform this activity are exposed to electrical hazards, ergonomic hazards and physical hazards, as they are constantly exposed to weather conditions, risk of accidents and falls, as they work at heights, in addition to possible musculoskeletal injuries. For the acquisition of information, an analysis of documents was carried out first, through the official websites of the institutions, magazines, newspapers, books and reports. For the data obtained from the representatives of the installing companies, a camera was used to record images, with a view to identifying them to be scored and to make it possible to draw up preventive measures. It was evident that the locations of installations followed in this study provided great risks to workers, in situations that could have been avoided if regulatory standards had been complied with or even investments aimed at adaptations, aiming at safety for this execution. The lack of organizational and risk management are capable of compromising the best protection measures. Therefore, the best way to address the issue is through emphasis on training and the importance of using Personal Protective Equipment, awareness and behavioral change while preserving one’s health.